High School Mathematics Enrichment Book to Facilitate Students' Problem-Solving Ability - Pradyumnati, Rahayu Malini; Harta, Idris (Al-Jabar: Jurnal Pendidikan Matematika, 2019)
This study aims to produce a mathematics enrichment book to facilitate problem-solving ability based on the aspects of validity, practicality, and effectiveness. The research method used is research and development using the ADDIE model which includes the analysis, design, development, implementation, and evaluation stages. The research instruments used consisted of validation sheets, practicality assessment sheets, and test questions for mathematical problem-solving abilities. Validity and practicality data analysis was carried out by converting the total score of quantitative data obtained into five-scale qualitative data. Effectiveness of data analysis is done by determining the percentage of the number of accomplished students and the average test scores of mathematical problem-solving ability. The result of the research is a valid, practical, and effective mathematics enrichment book to facilitate problem-solving ability. The mathematics enrichment book developed has met validity criteria based on the validators’ assessment with the average score in the high category, fulfills the practicality criteria based on the teachers’ assessment with the excellent category, and meets the effective criteria based on the results of the mathematical problem-solving ability with the percentage of students accomplishment of 79.5% and the average score of the test results of 79.